A Frame-semantic Approach to Co-occurrence Patterns: A Lexicographic Study of English and Greek Motion Verbs. (1st September 2018) - Dalpanagioti, Thomai
Abstract: This paper approaches co-occurrence patterns in lexicography from a frame-semantic perspective, using English and Greek motion verbs as a basis for discussion. After examining the wide spectrum of co-occurrence patterns (from the broad sense of typical contextual environment to the narrower sense of multi-word expressions), the paper focuses on the treatment of co-occurrence patterns in a bilingual pre-lexicographic database which is based on the principles of corpus linguistics and cognitive semantics (i.e. Frame Semantics and Conceptual Metaphor and Metonymy Theory). The polysemous verb fly is used as a case study to demonstrate how a frame-semantic approach to co-occurrence patterns facilitates the lexicographic tasks of establishing lexical units, describing multi-word expressions, and identifying cross-linguistic correspondences. The paper concludes by discussing the benefits of such an approach for lexicography (monolingual dictionaries, bilingual dictionaries and FrameNet).